Urinary vanin‐1 associated with chronic kidney disease in hypertensive patients: A pilot study. Issue 8 (9th August 2020) - Hosohata, Keiko; Matsuoka, Hiroyuki; Iwanaga, Kazunori; Kumagai, Etsuko
Abstract: Hypertension and chronic kidney disease (CKD) are serious interrelated public health problems. Despite the monitoring and control of high blood pressure, symptoms of CKD are not usually apparent in its early stages. Previously, we reported the utility of urinary vanin‐1 as an early biomarker of kidney injury in spontaneously hypertensive rats, but it remains unknown whether urinary vanin‐1 is associated with CKD in humans. In this study, we estimated associations between urinary vanin‐1 and parameters of kidney function in a cross‐sectional study of hypertensive patients. We measured concentrations of vanin‐1 using spot urine from 147 adult hypertensive patients (mean age, 72.8 years; 39.5% women). Patients were divided into 2 groups based on the median of the estimated glomerular filtration rate (eGFR). The group with eGFR < 60 mL/min per 1.73 m 2 showed significantly higher levels of urinary vanin‐1 than those with eGFR ≥ 60 mL/min per 1.73 m 2 . On univariate analysis, urinary vanin‐1 as well as neutrophil gelatinase‐associated lipocalin (NGAL) showed significant negative correlations with eGFR; however, multivariate analysis revealed that urinary vanin‐1, but not NGAL, significantly correlated with eGFR. In addition, urinary vanin‐1 had a significant positive correlation with the urinary protein‐to‐creatinine ratio (UPCR) ( r  = 0.21; P  = .021) and albumin‐to‐creatinine ratio (UACR) ( r  = 0.61; P  < .01). In conclusion, urinary vanin‐1 is associated with lower eGFR and higher UPCR and UACR, and might be a potential marker of decreased kidney function in hypertensive patients. Further studies are needed to confirm these findings.